Challenges and adoption strategies for cloud accounting information systems among SMEs: a conceptual perspective - Hamidan, Nur Dayana Balqis; San, Suzana (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Small and medium enterprises (SMEs) account for 98.5% of all businesses in Malaysia. Cloud accounting information systems is a digital tool to streamline SMEs’ operational business. Despite the advantages of cloud accounting information systems, SMEs have difficulty in leveraging the cloud system. Therefore, the objective of this conceptual study is to identify the challenges to the adoption of cloud accounting systems and propose strategies to enhance the effectiveness of the system to SMEs. The study found that low acceptance rates, limited technical expertise, financial constraints and data privacy and security are the barriers faced by SMEs in the adoption of cloud accounting information systems. To address these issues, continuous training and awareness programs, collaboration with professionals, government support, and protection of data security and privacy could alleviate the challenges of implementing cloud systems. The findings of this study could assist the SMEs owners and policy makers implementing strategies to achieve a smooth transition process towards cloud accounting information systems among SMEs.